The conservatives have no clothes : - Anrig, Greg (John Wiley & Sons, 2007)
Greg Anrig's wide-ranging and perceptive book looks beyond the ideology of the right and offers a persuasive account of the many policy failures that have emerged out of the conservative movement. Anrig has put the Bush administration and the right to a test that they themselves have carefully avoided. He has held them accountable not for their ideas, but for their performance.